Meningkatkan Hasil Belajar Bahasa Indonesia Melalui Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Pada Siswa Kelas XI Akuntansi SMK Muhammadiyah Watansoppeng - Rusbaena Rusbaena (Prodi PGSD FIP UNM, 2019)
This study aims to determine the improvement of student’s achievement of Indonesian Language at the grade XI Accounting of SMK Muhammadiyah Watansoppeng through cooperative learning models of the student teams achievement division (STAD) type. This research is a classroom action research which is carried out through four stages, namely planning, implementation, observation and reflection. The research subjects were class XI Accounting consisting of 15 people, namely 2 men and 13 women. The research procedure was carried out in a number of two cycles. The results of the study were analyzed by descriptive statistical techniques in the form of arithmetic averages and percentages. Based on data analysis, it was concluded that there was an increase in Indonesian language learning outcomes from cycle I to cycle II. In the first cycle the average student learning outcomes were 68.86 and in the second cycle it was 79.09. Similarly, the percentage of student learning completeness experienced an increase from the first cycle of 72.7% and in the second cycle to 100%.